Comparative Analysis Of 95MXC and SS420 Coatings Using Wire Arc Spray Method On Hardness and Microstructure Result - Saputra, Rudi; Abid Alfarizi, Muhammad (Greenation Research & Yayasan Global Resarch National, 2024)
Material coating technology is a method that is often applied to improve the mechanical properties and characteristics of a material. The materials often used in the coating process are metal materials, including medium carbon steel such as AISI 1045, which is often used as machine parts, light pressure gears, pinion forming dies, hydraulic shafts, pump shafts, piston rods. Coating materials vary greatly, this is adjusted to suit needs, such as the SS420 and 95MXC materials used because they have quite high wear resistance and corrosion resistance properties. The composition of the coating material and the strong current in the coating process can affect the quality of the coating results formed on the material. In this research, we will determine the wire with the best results using the wire arc spray method as a coating method to increase the mechanical properties of the PLTU boiler using 95 MXC and SS 420 wire. The highest hardness results were obtained for 95MXC wire with a value of 45.98 HRC. Meanwhile, the hardness value for SS420 wire is 33.11 HRC and the results of microstructure observations also show an increase in thickness of the 95MXC layer with a value of 297.99 ?m in line with the increase in hardness of the coating layer, because in a thicker coating layer the coating material particles will spread evenly and denser, thereby increasing the hardness value